Palangka Raya City Deforestation in 2006-2021 - Iskandar, Beni; Marlina, Sari; Nathaneal, Laondry (Prosiding University Research Colloquium, 2023)
Central Kalimantan is the province with the second highest deforestation rate in Indonesia. Palangka Raya City is the capital city of Central Kalimantan Province, which continues to experience population growth and land investment. Monitoring deforestation needs to be done to provide basic information for sustainable forest management planning. This study aims to analyze deforestation and the concentration of deforestation in Palangka Raya City for the period 2006-2021. This research uses the method of overlaying land cover, map validation, hisotric analysis of deforestation and the concentration of deforestation. This research shows that the accuracy of the deforestation map is 90% overall accuracy and 80% kappa accuracy, deforestation in Palangka Raya City is 7,810 ha in the 2006-2011 period, increased by 17,452 ha in the 2011-2016 period, and decreased by 10,121 ha in the 2016-2021 period, the concentration of deforestation in Palangka Raya City is in Rakumpit and Bukit Batu districts. This research can serve as basic information to support sustainable forest management planning in Palangka Raya City.